Race Defamation: A Postcolonial Reading of Derek Walcott’s Dream on Monkey Mountain - Fatah, Shokhan Mohammed (Al-Adab Journal, 2023)
As a postcolonial text, Dream on Monkey Mountain depicts the colonial discourses regarding the black. Derek Walcott has vividly presented the sufferings of the black in his play. The inferiority of the black is explicitly reflected in which the white is superior and the black is less than human beings. The best method to approach this text is from a postcolonial viewpoint. Major postcolonial concepts such as othering, mimicry and hybridity. The importance of this study is that major postcolonial legacies are mirrored in this play. The portrayal of racism and the weakness of the blacks are openly presented.